Backhaul Utilization Trend and Trucks Turnaround Time (TAT) in Indian Logistics System - Mohamed Jasim K; Jayshree Suresh; Reena Murray (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to provide insights on the validation of the efficiency of TAT and Backhaul in Indian logistics system. Both exploratory and analytical research design was adopted for this research study. Logistics managers in selected sectors were chosen as samples for the study. Cluster sampling method was adopted to derive 186 samples from the Universe. A self-administered structured Questionnaire was used to collect primary data. This research study would contribute to the existing body of knowledge or literature by advancing the understanding of TAT and Backhaul in Indian logistics system. To validate efficiency of TAT and Back Haul in Indian logistics system, the researchers have studied only the selected factors. The study indicated that the factors influencing to validate efficiency of TAT and Backhaul in Indian logistics system undertaken for the study are: cost estimation, forecasting, reduction in procurement cost, avoid wastages, reduce manpower, outbound logistics relations, internal relations between logistics and material manager.